THE CHARACTERISTICS OF ADOLESCENTS NASOPHARYNGEAL CARCINOMA PATIENTS IN MOHAMMAD HOESIN GENERAL HOSPITAL PALEMBANG JANUARY 2013-DECEMBER 2017 - Melania; Denny Satria Utama (INTERNATIONAL JOURNAL OF NASOPHARYNGEAL CARCINOMA, 2019)
Abstract Introduction: Nasopharyngeal carcinoma is (NPC) mostly found in men of productive age with a ratio of men and women 2,18: 1 and 60% of patients age between 25 and 60 years. NPCs are very rarely found in adolescents, namely age 11 to 21 years. Objective: To determine the characteristics of nasopharyngeal carcinoma in adolescent patients at ORL-HNS Department of Dr. Mohammad Hoesin General Hospital Palembang. Method: This is a descriptive retrospective study. The sample is all patients diagnosed with NPC in adolescence at ORL-HNS Department of Dr. Mohammad Hoesin General Hospital Palembang in January 2013 to December 2017 period. Results: In this study, the number of adolescent NPC patients from January 2013 to December 2017 was 12 patients. The majority of adolescent NPC patients were male (66,6%). The most common histopathological finding was WHO 2B (50%). Based on the T category, largely, the patients were T4 (41,6%). Most patients with Nodules were N3 (58,3%) and came to the ENT clinic were already in stage IV (41,6%). Conclusion: Adolescent nasopharyngeal carcinoma is more common in men than women (2: 1), and shows a response to proper therapy.